Looking for reliable answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
Answer:
Step-by-step explanation:
[tex]\left\{\begin{array}{ccc}f(x)&=&3x+a\\g(x)&=&b-5x\\g(f(1))&=&2\\g^{-1}(7)&=&1\\\end{array}\right.\\\\\\g(f(x))=g(3x+a)=b-5(3x+a))=b-15x-5a\\g(f((1))=b-15-5a=2\\\\\\g(x)=y=b-5x\\x=b-5y\\5y=b-x\\y=\dfrac{b-x}{5} \\g^{-1}(x)=\dfrac{b-x}{5} g^{-1}(7)=\dfrac{b-7}{5} =1\\b-7=5\\\\\boxed{b=12}\\\\\left\{\begin{array}{ccc}b&=&12\\5a-b&=&-17\\\end{array}\right.\\\\\\\left\{\begin{array}{ccc}b&=&12\\5a-12&=&-17\\\end{array}\right.\\\\\\[/tex]
[tex]\left\{\begin{array}{ccc}a&=&-1\\b&=&12\\\end{array}\right.\\\\\\[/tex]
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.